الطبيعة القانونية للعقود الذكية وتطورها في القانون العراقي والايراني والأردني. - غ ي ث ع ب دالك ي م ج ا; علي العلوي القزو (Journal of Babylon Center for Humanities Studies, 2026)
This study examines the legal nature of smart contracts and their evolution within the Iraqi, Iranian, and Jordanian legal systems, in light of the digital transformation and Blockchain technology. The study aims to determine the legal classification of smart contracts, considering the absence of explicit legislative regulation, and to discuss their applicability to the traditional contract theory, while analyzing their advantages and disadvantages. It is revealed that smart contracts are selfexecuting digital agreements based on programmed conditions (if…then), and are considered full-fledged legal contracts despite the difference in the means of expression and the mechanism of execution. These contracts often fall within the scope of adhesion contracts due to their connection to standardized, ready-made agreements. Legislatively, the laws of Iraq, Iran, and Jordan have not explicitly addressed smart contracts, but they have provided a preliminary framework through electronic transactions and signatures laws. The study concludes that these countries are still in an early foundational stage regarding the regulation of smart contracts, necessitating legislative intervention to resolve issues related to self-execution, central control, and the protection of contracting parties' rights. Introduction The digital revolution has given rise to "smart contracts," computer programs that automatically execute contract terms on blockchain platforms. This technological development has raised a fundamental legal question regarding the legal nature of these contracts. The smart contract lies at the intersection of the rapidly evolving digital world and the established legal world, prompting the question: can it be included within the traditional definition of a contract in civil law? Or is it a new entity requiring its own specific legal framework?.